A Newborn Infant with Congenital Central Hypoventilation Syndrome and Pupillary Abnormalities: A Literature Review - Mimily Harsono; Sandeep Chilakala; Shiva Bohn; Eniko K. Pivnick; Massroor Pourcyrous (Thieme Medical Publishers, Inc., 2022)
We present a neonate with early onset apnea and bradycardia in the absence of primary cardiorespiratory and central nervous system disorders that eventually required chronic ventilator support starting at 6 hours of life. Molecular testing of paired-like homeobox 2b (PHOX2B) gene mutation confirmed the diagnosis of congenital central hypoventilation syndrome (CCHS). CCHS is a rare genetic disorder characterized by impaired central respiratory control with or without broad spectrum of autonomic nervous system (ANS) dysregulations. Ocular ANS dysregulation is a rare finding in CCHS individuals, and it is usually discovered later in life. However, the ophthalmic evaluation of this neonate on first day of life revealed persistent mild dilated oval pupils with limited light reactivity.